Foreign Body Extraction of a Push-pin nail with Granulation Tissue Complication on a Thirteen Years Old Male - octavia, umi fatma; Putra, Ngakan Putu Parsama (Universitaas Brawijaya, 2021)
Background : Foreign body aspiration is common in children (80% in children under 5 years old) and elderly. The ratio in men is higher than in women. Flexible bronchoscopy is often used as a primary procedure in such cases because of its high sensitivity and specificity. However, in some cases, rigid bronchoscopy might be superior. This is a case report about a patient who came with complaints of bloody cough and chest pain after the ingestion of a push-pin nail. The patient underwent both bronchoscopic procedures.Case : A 13-year-old male presented with complaints of sudden bloody coughing accompanied by chest pain in the middle area. Physical examinations were unremarkable, but images of spikes suggestive of a foreign object on the left hilus were found at the chest x-ray. A flexible fiberoptic bronchoscopy was performed immediately. A push-pin nail, located the left main bronchus with a sharp tip embedded in the mucosa and covered by granulation tissue, was identified. Evacuation attempts were unsuccessful. Rigid bronchoscopy was then performed and evacuation was carried out successfully. The patient was then discharged after forty-eight hours of close monitoring.Conclusion: There are two types of bronchoscopy, flexible and rigid. Both have their respective advantages in the handling of patients with foreign bodies. Â Acquiring skills in operating both types of bronchoscopy are important for a bronchologist.Keywords: Foreign body, Aspiration, Granulation tissue, Bronchoscopy